2018
DOI: 10.1111/den.13028
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid procedure combining endoscopic gallbladder lavage and internal drainage with elective cholecystectomy for acute cholecystitis: A prospective pilot study (The BLADE study)

Abstract: http://www.umin.ac.jp/ctr/index.htm (ID: UMIN-000009680).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Another strategy described in the BLADE study, combining ETGBD and endoscopic gallbladder lavage with elective cholecystectomy, could be considered in patients with acute cholecystitis fit for surgery. 29 Overall technical and clinical success rates in our study were 97.2% and 91.7%, respectively. These results are similar to those reported in a recently published systematic review including 226 patients from nine case series, 30 where technical and clinical success rates were 95.1% and 91.6%.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Another strategy described in the BLADE study, combining ETGBD and endoscopic gallbladder lavage with elective cholecystectomy, could be considered in patients with acute cholecystitis fit for surgery. 29 Overall technical and clinical success rates in our study were 97.2% and 91.7%, respectively. These results are similar to those reported in a recently published systematic review including 226 patients from nine case series, 30 where technical and clinical success rates were 95.1% and 91.6%.…”
Section: Discussionmentioning
confidence: 47%
“…This combined approach might also be useful in patients with relapsing cholangitis or choledocholithiasis despite previous sphincterotomy or patients with complex malignant biliary obstruction. Another strategy described in the BLADE study, combining ETGBD and endoscopic gallbladder lavage with elective cholecystectomy, could be considered in patients with acute cholecystitis fit for surgery …”
Section: Discussionmentioning
confidence: 99%
“…Although ETGBD with ENGBD or EGBS is an effective alternative method when emergency cholecystectomy and PTGBD are considered high risk 1 2 3 4 5 , ETGBD is technically difficult. In the last 10 years, the technical success rate is reported to be 64 % to 96 % 5 6 7 8 9 12 13 14 15 16 17 18 19 20 . ETGBD’s technical difficulty is associated with the inherent complexity of inserting the GW into the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical success rates with ETGBD for acute cholecystitis are reported to be 83 % to 100 % in per-protocol analyses 5 6 7 8 9 12 13 14 15 16 17 18 19 20 21 . It has also been reported that the clinical success rate with ETGBD is roughly 10 % lower than the technical success rates in intention-to-treat analysis because of the accumulation of purulent material, sludge, or gallstones, thus hindering effective drainage 13 22 23 .…”
Section: Discussionmentioning
confidence: 99%
“…6). Finally, we placed a modified 5F, 13-cm single-pigtail plastic stent created by cutting nasobiliary tube 7 (Gadelius Medical Co, Ltd, Tokyo, Japan) into the gallbladder (Fig. 7).…”
mentioning
confidence: 99%